The Effects of Chromium Supplementation on Gene Expression of Insulin, Lipid, and Inflammatory Markers in Infertile Women With Polycystic Ovary Syndrome Candidate for in vitro Fertilization: A Randomized, Double-Blinded, Placebo-Controlled Trial - Amiri Siavashani, Mehrnush; Zadeh Modarres, Shahrzad; Mirhosseini, Naghmeh; Aghadavod, Esmat; Salehpour, Saghar; Asemi, Zatollah (Frontiers in Endocrinology, 2018)
Purpose: This study was performed to determine the effects of chromium supplementation on the gene expression of insulin, lipid, and inflammatory markers in infertile women with polycystic ovary syndrome (PCOS) who were candidate for in vitro fertilization (IVF). Methods: Forty women, aged 18-40 years, who had been selected for IVF were recruited in this randomized double-blinded, placebo-controlled trial. They (n=20/group) were randomly assigned into intervention groups to take either 200 µg/day of chromium or placebo for 8 weeks. Inflammatory markers were measured at baseline and end of the trial. Genes related to insulin, lipid and inflammation were expressed in peripheral blood mononuclear cells (PBMCs), using RT-PCR method. Results: Chromium supplementation led to a significant reduction in serum high sensitivity C-reactive protein (hs-CRP) (-1.4±1.5 vs. +0.2±2.2 mg/L, p=0.01), compared with placebo. RT-PCR findings indicated that chromium supplementation upregulated gene expression of peroxisome proliferator-activated receptor gamma (PPAR-γ) (p=0.01), glucose transporter 1 (GLUT-1) (p=0.001) and low-density lipoprotein receptor (LDLR) (p=0.01), as well as downregulated gene expression of interleukin-1 (IL-1) (p=0.004) in PBMCs of patients with PCOS rather than placebo. Chromium supplementation had no significant effect on gene expression of IL-8, tumor necrosis factor alpha (TNF-α), transforming growth factor beta (TGF-β) and vascular endothelial growth factor (VEGF). Conclusion: Overall, our findings documented that infertile women with PCOS, who were candidate for IVF benefited from chromium supplementation for 8 weeks in terms of lowering hs-CRP and improving the gene expression of PPAR-γ, GLUT-1, LDLR and IL-1, though chromium had no effect on gene expression of IL-8, TNF-α, TGF-β and VEGF.